Biografi Tun Abdul Razak: Negarawan dan Patriot oleh Nik Anuar Nik Mahmud, Muhammad Haji Salleh dan Abd. Ghapa Harun. Bangi, Selangor: Penerbit Universiti Kebangsaan Malaysia dan Yayasan Tun Razak, 2011, 401 pp. - Abu Talib Ahmad (Kajian Malaysia, 2014)
Tun Abdul Razak Dato' Hussein is remembered by Malaysians as the "father of development." In fact he was closely associated with development and changing the mindset of the rural Malays since 1955 when he was acting as Chief Minister (Menteri Besar) of Pahang. His name is synonymous with efforts to ameliorate rural poverty through the construction of roads, bridges, community centres, adult education, clinics and midwifery centres and Federal Land Development Authority (FELDA). Due to his intimacy with the rural constituency commentators have pointed him as pro-Malay unlike the Tunku which many identified with multiculturalism. But Tun Abdul Razak is equally close to other facets of national development that are urban based. He has been described as an introvert, shy and unassuming, but a man who was firm and possessed a deep sense of purpose. He was equally known for his sense of humor although this side of him was often hidden from the public gaze. Former civil servants who served under him remembered "his minutes, comments while his speeches were simple, short and to the point of reflecting his reticence." 1 Others marveled at his firm grasp of management, and his personal style in dealing with government officers especially at the district level.2 He lacked charisma and was a poor orator but there is much intellectual substance in his speeches. Yet towards the end of his life, he had to grapple with opposition within United Malays National Organisation (UMNO) and from Tun Datu Mustapha Datu Harun, the Sabah strongman. This followed a struggle for power in UMNO soon after the demise of his deputy, the capable and highly principled Tun Dr. Ismail Abdul Rahman, in August of 1973.3 He was weighed down both by the coterie of his inner circle, which failed to provide effective advice, and by his deteriorating health.4